Review of clinical characteristics and mortality outcomes in patients on maintenance hemodialysis during the Omicron surge: a single center experience - Yiyang Xue; Weiwei Feng; Ling Shi; Ning Cui; Wei Zhang; Junxiu Dong; Chunying Li; Jinjin Hu; Junjun Wei (BMC, 2024)
Abstract Background This hemodialysis center experienced the pandemic from December 2022 to January 2023. Therefore, we sought to describe the clinical characteristics and mortality outcomes in hemodialysis patients during this Omicron surge. Methods According to whether they are infected, they are divided into two groups: SARS-CoV-2-positive and SARS-CoV-2-negative. The SARS-CoV-2-positive group was divided into a survival group and a non-survival group for comparison. Results 366 of 457 hemodialysis patients were infected with SARS-CoV-2. The most common symptoms observed were fever (43.2%) and cough (29.8%), Followed by diarrhea (1.4%). Hemodialysis patients with hypertension were more susceptible to SARS-CoV-2 infection. The lymphocyte count, serum creatinine, serum potassium, and serum phosphorus in the SARS-CoV-2-positive group were significantly lower than those in the SARS-CoV-2-negative group. The all-cause mortality rate for infection with SARS-CoV-2 was 5.2%. Only 7 of 366 SARS-CoV-2-positive patients were admitted to the intensive care unit, but 6 of them died. Intensive care unit hospitalization rates were significantly higher in the non-survival group compared with the survival group. White blood cells count, neutrophil count, C-reactive protein, AST, and D-dimer in the non-survival group were higher than those in the survival group. The lymphocyte count, hemoglobin concentration, serum creatinine, serum albumin, serum phosphorus and parathyroid hormone in the non-survival group were lower than those in the survival group. Age > 65 years, elevated C-reactive protein and AST are independent risk factors for death. Finally, no significant difference in vaccination status was found between the SARS-CoV-2-positive group and the negative group. Conclusions Hemodialysis patients are at high risk for SARS-CoV-2 infection. Ensuring the adequacy of hemodialysis treatment and maintaining good physical condition of patients are the top priorities.